A Role for Epitope Networking in Immunomodulation by Helminths - Homan, E. Jane; Bremel, Robert D. (Frontiers in Immunology, 2018)
Helminth infections, by nematodes, trematodes or cestodes, can lead to modulation of host immune responses. This allows long-duration parasite infections and also impacts responses to co-infections. Surface, secreted, excreted and shed proteins are thought to play a major role in modulation. A commonly reported feature of such immune modulation is the role of T-regulatory cells and IL-10. Efforts to identify helminth proteins which cause immunomodulation have identified candidates, but not provided clarity as to a uniform mechanism driving modulation. In this study we applied a bioinformatics systems approach, allowing us to analyze predicted T cell epitopes of 17 helminth species, and the responses to their surface proteins. In addition to MHC binding, we analyzed amino acid motifs that would be recognized by T cell receptors (T cell exposed motifs). All the helminth species examined have, within their surface proteins, peptides which combine very common T cell exposed motifs with predicted high affinity binding to many human MHC alleles. This combination of features would result in large cognate T cell, and a high probability of eliciting T-regulatory responses. The T cell exposed motifs, which determine recognition by responding T cell clones, are shared to a high degree between helminth species and with Plasmodium falciparum and Mycobacterium tuberculosis, both common co-infecting organisms. The implication of our observations is that T-regulatory cells not only play a significant role in helminth-induced immune modulation, but also that the epitope specificities of T-regulatory responses are shared across species and genera of helminth. Hence, the immune response to a given helminth cannot be considered in isolation, but rather forms part of an epitope ecosystem, or microenvironment, in which potentially immunosuppressive peptides in the helminth network via their common T cell receptor recognition signals with T cell epitopes in self proteins, microbiome, in other helminths, and in taxonomically unrelated pathogens. Such a systems approach provides a high-level view of the antigen-immune system signaling dynamics that may bias a host’s immune response to helminth infections towards immune modulation. It may indicate how helminths have evolved to select for peptides that favor long term parasite host coexistence.